The behavioral biases of Muslims in Islamic banking and finance: a second-order self-reported religiosity measurement invariance - Adewale, Abideen Adeyemi; Haron, Razali (IIUM Press, International Islamic University Malaysia, 2016)
This study examines a measurement invariance of a second-order factor model of the behavioral biases in Islamic banking and finance activities among Muslims in Malaysia. Data elicited via a survey questionnaire was subjected to structural equation modeling analysis using the Amos 23.0 software. The study revealed that behavioral biases as a second-order factor is indicated by herding, cognitive dissonance, anchoring, regret aversion and overconfidence of first order factors. Measurement invariance was tested based on self-reported religiosity across a number of hierarchically structured invariance analysis models, including configural at the first-order level, metric, intercepts, and residuals at both the first-order and second-order levels. A significant variance was observed between the high and low self-reported religiosity groups. However, no difference was observed between the two groups and the ‘moderate’self-reported religiosity groups. Furthermore, based on the critical ratio score of statistical significance at alpha of 0.001, the latent mean difference tests of the second-order model indicates statistical significance across groups based on a path-by-path analysis.